A high thermal conductivity, self-lubricating insulating coating and preparation method thereof
By introducing aluminum nitride and boron nitride nanoparticles into the alumina powder and adopting a controlled atmosphere plasma spraying process, the problems of low thermal conductivity of the alumina insulating coating and insufficient thermal stability of the material are solved, and high thermal conductivity is achieved and improve self-lubricating performance.
Patent Information
- Application Number
- CN202410469090.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-04-18
AI Technical Summary
The thermal conductivity of the existing alumina insulating coatings is low, and the thermal stability of aluminum nitride and boron nitride materials is insufficient under high temperature conditions, resulting in reduced deposition efficiency and uneven composition, which affects the thermal conductivity of the coating and Self-lubricating performance.
A specific powder making method combined with plasma beam thermal spraying method is used to introduce aluminum nitride and boron nitride nanoparticles into alumina powder, and the coating is prepared through a controlled atmosphere plasma spraying process to achieve thermal conductivity and self-lubricating properties. promote.
The thermal conductivity and self-lubricating properties of the insulating coating were successfully improved, and the oxidation and decomposition of aluminum nitride and boron nitride at high temperatures were avoided, ensuring the uniformity and performance of the coating composition.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder material and surface coating processing, and in particular relates to a high thermal conductivity, self-lubricating insulating coating and a preparation method thereof. Background Art
[0002] Alumina coatings are widely used in electronics, electrical, semiconductor, motor and other fields due to their excellent insulation properties and chemical stability. However, the low thermal conductivity of traditional alumina insulation coatings limits their application in dynamic insulation components in high-power and high-heat dissipation environments. Therefore, improving the thermal conductivity of alumina coatings and increasing the self-lubricating properties of the contact surface while maintaining its electrical insulation has become a very valuable research point.
[0003] Aluminum nitride is a covalently bonded compound with a hexagonal zirconite-type structure. The crystal structure of aluminum nitride determines its excellent thermal conductivity, insulation, and dielectric properties. According to the study of "Study on Tape Casting and Sintered Body Performance of Aluminum Nitride Ceramics", the two elements that make up the aluminum nitride molecule have small atomic weights, a relatively simple crystal structure, good harmonicity, and a short Al-N bond with large bond energy. The resonance of the covalent bond is conducive to the phonon heat transfer mechanism, making aluminum nitride materials have thermal conductivity superior to that of general non-metallic materials. Compared with other ceramic materials, aluminum nitride structural ceramics have good mechanical properties, high hardness, and better toughness than alumina ceramics.
[0004] Boron nitride c-BN is a wide bandgap semiconductor material with high thermal conductivity, high resistivity, high mobility, low dielectric constant, high breakdown electric field, the ability to achieve dual-type doping and good stability. Boron nitride is also used in self-lubricating coatings due to its obvious lubricating effect.
[0005] At present, the modification of aluminum oxide coating is mostly for the purpose of toughening, but there are few reports on the use of plasma spraying method to prepare coating and add aluminum nitride and boron nitride to improve the thermal conductivity and lubricity of aluminum oxide insulating coating. Because aluminum nitride and boron nitride materials have lower thermal stability than oxide ceramics, they will oxidize, decompose and volatilize due to high temperature during spraying, which reduces the deposition efficiency of the two, and the internal composition of the coating is uneven, which affects the thermal conductivity and self-lubricity of the coating. How to use aluminum nitride, boron nitride and aluminum oxide powder to prepare a coating with high thermal conductivity and self-lubricity is an urgent problem to be solved in this field.
[0006] In terms of powder preparation, most studies use wet chemical methods such as sol-gel and coprecipitation to pre-coat the mixed powder slurry on the surface of the substrate, and then perform subsequent curing treatment to form a coating. CN109369158 discloses a coagulation method, in which only aluminum nitride powder is added to aluminum oxide, but does not reflect the specific method of subsequent coating processing and preparation. CN114774911 discloses that aluminum oxide, boron nitride and cerium oxide are mixed into a slurry with an organic solvent polyvinyl pyrrolidone aqueous solution, and then coated on the surface of the workpiece, and then formed by laser cladding. CN115820009 A shows a solution of mixing aluminum nitride, boron nitride, aluminum oxide and polymethyl methacrylate and stirring to form a slurry; applying the slurry to the surface of the parts and drying to form a coating. CN116376321A discloses a coating method to prepare an aluminum oxide coating layer on the surface of hexagonal boron nitride composite powder. This invention scheme only includes boron nitride powder, and there is no evidence to show whether the powder is suitable for thermal spraying. Among other existing technologies, there are hot pressing sintering methods, and various plasma-assisted deposition methods such as CVD and PVD, which can only obtain a single layer of boron nitride or a boron nitride-containing phase film under vacuum conditions, and there are also problems such as complex process, long time consumption, high cost, and some special parts are not suitable for direct placement in the coating preparation container for overall heating to achieve coating deposition. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a high thermal conductivity, self-lubricating insulating coating and a preparation method thereof. The present invention combines a specific powder making method with a plasma beam thermal spraying method, introduces aluminum nitride and boron nitride nanoparticles into aluminum oxide powder, and uses argon Ar as an atmosphere protective gas while preparing the coating by plasma spraying process, successfully preparing the coating while achieving the improvement of thermal conductivity and self-lubricating performance.
[0008] The technical solution of the present invention is as follows:
[0009] The first aspect of the present invention provides a method for preparing a high thermal conductivity, self-lubricating insulating coating, the preparation method comprising the following steps:
[0010] S1: After cleaning and drying the substrate, the substrate is subjected to surface treatment and then used for standby;
[0011] S2: spraying the powder material on the surface of the substrate treated in step S1 to obtain an insulating layer;
[0012] S3: Sealing treatment to obtain a high thermal conductivity, self-lubricating insulating coating.
[0013] Preferably, in step S1, the surface treatment is performed by sandblasting to roughen and activate the surface; the pressure of the sandblasting is 0.1-0.6 MPa, and the distance of the sandblasting is 30-140 mm.
[0014] Preferably, in step S2, the spraying is performed by controlled atmosphere plasma spraying, wherein argon is used as the main gas and the protective gas, and hydrogen is used as the auxiliary gas.
[0015] Preferably, the parameters of the controlled atmosphere plasma spraying are: current 300-650A, voltage 50-80V, auxiliary gas flow rate 1-15L / min, scanning speed 150m / min, powder feeding amount 20-150g / min, powder feeding carrier gas flow rate 2.0-12.0L / min, main gas flow rate 25-75L / min, main gas pressure 0.3-0.8MPa, auxiliary gas pressure 0.5-0.8MPa, spraying distance 100-250mm, spraying angle 70-90°, and pressure in the spraying chamber 0.5-1.0Mpa.
[0016] Preferably, during the spraying process, the temperature of the substrate surface is ≤150°C.
[0017] Preferably, the powder material is prepared by:
[0018] S2-1: premixing aluminum oxide powder, aluminum nitride powder, and boron nitride powder to obtain a premixed powder;
[0019] S2-2: subjecting the premixed powder and the additive to three-stage high-speed mechanical coating and powdering in an extrusion reactor to obtain mechanical pre-coated powder.
[0020] S2-3: The mechanical pre-coated powder of step S2-2 is mixed with the precursor solution, and then spray-dried to obtain a coated powder material.
[0021] Preferably, in step S2-1, the premixing is ball milling mixing; the ball milling time is 8-15 hours, and the ball milling medium is alumina balls.
[0022] Preferably, the premixed powder comprises the following components by mass percentage: 15%-25% aluminum nitride, 10%-25% boron nitride, and 50%-75% aluminum oxide; wherein the particle size of aluminum oxide is 1-50 μm, the particle size of boron nitride is 0.1-5 μm, and the particle size of aluminum nitride is 0.1-5 μm.
[0023] Preferably, in step S2-2, the selected auxiliary agent is a binder; the binder accounts for 1%-10% of the total mass of the premixed powder and the binder.
[0024] Preferably, the three-stage high-speed mechanical coating comprises: a first stage mechanical coating, a second stage mechanical coating and a third stage mechanical coating;
[0025] in,
[0026] The mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v1 is 500-1600 r / min, and the coating time t1 is 10-30 min;
[0027] The mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v2 is 1500-2500 r / min, and the coating time t2 is 5-10 min;
[0028] The mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v3 is 800-1500 r / min, and the coating time t3 is 6-15 min;
[0029] In the three-stage highly mechanical coating powder making, the rotor speed and coating time satisfy the following relationship: v1<v3<v2, and t1>t3>t2.
[0030] Preferably, in step S2-3, the mass ratio of the mechanical pre-coated powder to the precursor solution is 1:(1-9); the precursor solution is a mixture of a sodium carbonate solution and an aluminum nitrate solution to obtain a precursor solution containing aluminum hydroxide flocculent precipitate; the mass concentration of the sodium carbonate solution is 25-35%; the concentration of the aluminum nitrate solution is 0.6-1.5 mol / L.
[0031] Preferably, the parameters of the spray granulation tower are set as follows: furnace temperature is 100-170°C, air outlet temperature is 180-250°C, and atomizing disk rotation speed is 20-40r / s.
[0032] Preferably, the coated powder material comprises, from the inside to the outside, an inner aluminum oxide layer, an aluminum nitride-boron nitride layer, and an outer aluminum oxide layer; the thickness of the outer aluminum oxide layer is 2-12 μm.
[0033] Preferably, the particle size of the coating powder material is 15-100 μm.
[0034] The second aspect of the present invention protects a high thermal conductivity, self-lubricating insulating coating prepared by the preparation method described in the first aspect, wherein the thickness of the coating is 0.10-1.2 mm.
[0035] The beneficial technical effects of the present invention are:
[0036] The present invention achieves sandwich coating of boron nitride and aluminum nitride by mechanically coating fine particles of boron nitride and aluminum nitride on the surface of a powder with aluminum oxide as a core skeleton in advance, and then coating the surface of the obtained coated powder with a layer of aluminum oxide film by a chemical coating method, and then thermally spraying the pretreated substrate surface with a plasma beam in a controlled atmosphere, successfully introducing aluminum nitride and boron nitride particles into the aluminum oxide powder, and preparing a coating by spraying, thereby achieving the improvement of thermal conductivity and self-lubricating performance of the insulating coating.
[0037] The present invention firstly adopts a high-speed mechanical fusion method for coating, thereby realizing the compact coating of the main skeleton alumina powder with aluminum nitride and boron nitride powder; the process is to extrude the particles by using an extrusion head through high-speed mechanical fusion, realize the complete coating of the coating layer by the adhesive, improve the density and compactness of the coating layer, and avoid the adhesion between the powder particles by setting the distance of the extrusion head and the speed of mutual movement with the kettle wall, so that the powder can be firmly adhered to the mother particles in a short time to form composite particles. At the same time, chemical coating is further adopted after mechanical coating. The primary powder of aluminum nitride and boron nitride coated alumina core obtained by mechanical mixing coating is mixed with the precursor solution, spray granulation is performed, and aluminum hydroxide is dehydrated to become aluminum oxide, thereby obtaining alumina-coated aluminum nitride and boron nitride mechanically coated composite powder containing alumina core. This avoids the thermal decomposition or oxidation of aluminum nitride and boron nitride due to the high-temperature plasma beam during the spraying process, while improving the effective deposition rate of boron nitride and aluminum nitride in the coating, and ensuring to the greatest extent that the content of aluminum nitride and boron nitride in the coating is close to the content in the body. DETAILED DESCRIPTION
[0038] The present invention will be described in detail below in conjunction with the embodiments.
[0039] When directly thermally sprayed based on the existing plasma process, aluminum nitride and boron nitride materials have lower thermal stability than oxide ceramics. During spraying, they will be oxidized, decomposed and volatilized due to high temperature, which reduces the deposition efficiency of the two and makes the internal composition of the coating uneven, affecting the thermal conductivity and self-lubricating properties of the coating. This application successfully introduces aluminum nitride and boron nitride nanoparticles into aluminum oxide powder through a specific powdering method and a plasma beam thermal spraying method, and uses a plasma spraying process to prepare a coating to achieve the improvement of the thermal conductivity and self-lubricating properties of the insulating coating.
[0040] The first aspect of the present invention provides a method for mechanically mixing and coating powders, wherein the coating method of the powders is:
[0041] S2-1: premixing aluminum oxide powder, aluminum nitride powder, and boron nitride powder to obtain a premixed powder;
[0042] S2-2: subjecting the premixed powder and the additive to three-stage high-speed mechanical coating and powdering in an extrusion reactor to obtain mechanical pre-coated powder.
[0043] S2-3: After mixing the mechanical pre-coated powder of step S2-2 with the precursor solution, spray drying is carried out in a spray granulation tower to obtain a coated powder material. The coated powder is a composite powder of aluminum nitride and boron nitride containing an aluminum oxide core coated with aluminum oxide.
[0044] In some embodiments of the present invention, in step S2-1, the premixing is performed by ball milling in a planetary ball mill, the ball milling time is 8-15 hours, and the ball milling medium is alumina balls.
[0045] In some embodiments of the present invention, the multi-component powder comprises, by mass percentage, 15%-25% aluminum nitride, 10%-25% boron nitride, and 50%-75% aluminum oxide; wherein the aluminum oxide powder is used as the main material with a particle size of 1-50 μm, and the powder particle size of boron nitride and aluminum nitride is 0.1-5 μm; the coating prepared therefrom also mainly serves as the basic framework.
[0046] In some embodiments of the present invention, the selected auxiliary agent is mainly a binder; the binder includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, gum arabic, cyclodextrin, epoxy resin, carboxymethyl cellulose, sodium metasilicate, and alkyd varnish; the present application does not limit the type of binder, and any binder that can meet the requirements of the present application is within the scope of protection of the present application. The mass fraction of the binder in the total raw materials (total mass of the binder and the premixed powder) is 1%-10%.
[0047] In some embodiments of the present invention, the three-stage high-speed mechanical coating in step S2-2 includes: a first stage mechanical coating, a second stage mechanical coating and a third stage mechanical coating.
[0048] In some embodiments of the present invention, the mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v1 is 500-1600 r / min, and the coating time t1 is 10-30 min.
[0049] In some embodiments of the present invention, the mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v2 is 1500-2500 r / min, and the coating time t2 is 5-10 min.
[0050] In some embodiments of the present invention, the mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v3 is 800-1500 r / min, and the coating time t3 is 6-15 min.
[0051] It can be understood that step S2-2 is the powder mixing stage. In order to ensure that the powder is fully mixed and improve the time efficiency of powder mixing, in the three-stage high-speed mechanical coating powder making of the present invention, the rotation speed of the rotor satisfies the following relationship: v1<v3<v2, and t1>t3>t2.
[0052] The powder coating method of the present invention can efficiently obtain highly compact coated powder, and the coating state is relatively complete, which helps the powder to achieve applicability in thermal spraying processes.
[0053] It can be understood that, based on the conventional mechanical coating process, the present invention applies extrusion force to the particles through the extrusion head during the coating process, so as to achieve complete coating of the coating layer by the binder, improve the density and compactness of the coating layer, and apply shear force to the material through the high-speed mutual movement of the extrusion head and the kettle wall at an appropriate distance, thereby avoiding adhesion between the composite particles; the sub-particles can be firmly adhered to the mother particles to form composite particles in a short time, and the sphericalization of the composite particles can be completed at the same time of composite formation; wherein, the first stage is the solid-liquid mixing stage, and medium-speed coating is adopted, and medium speed is adopted to stir the material, so as to achieve the binder and The premixed powder is evenly mixed; the second stage is the semi-solid stage or the block solid stage, during which the concentration of the material binder increases, and the friction between the materials, between the stirring extrusion head and the materials, and between the kettle wall and the materials is increased through high-speed rotation, so that the finer particles are evenly and tightly coated on the surface of the coarser powder; the third stage is the powdery solid stage, during which the adhesion between the particles is broken to form powder, and a slower speed is used for stirring. The shear force is applied to the material through the high-speed mutual movement of the extrusion head and the kettle wall at an appropriate distance, thereby avoiding adhesion between the composite particles, and the coating time needs to be controlled at this stage to avoid the completely coated particles from being broken again.
[0054] It is understandable that compared with the traditional mechanical coating process commonly used in the preparation of single-component coated powders, the coating structure cannot be achieved when preparing two-component coated skeleton component powders, and the three-component components often agglomerate, and the powder agglomeration structure is easy to loosen. The high-speed mechanical fusion preparation method proposed in the present invention realizes the compact coating of aluminum nitride and boron nitride multi-component powders with the main skeleton alumina powder, and successfully solves the process adaptability and efficiency of aluminum nitride and boron nitride in the preparation of thermal spray powders. It can meet the application requirements of components in high power, high heat dissipation, rolling and sliding friction conditions, and harsh insulation environments.
[0055] In some embodiments of the present invention, in step S2-3, the mass ratio of the mechanical pre-coated powder to the precursor solution is 1:1-9; the precursor solution is a mixture of a sodium carbonate solution and an aluminum nitrate solution to obtain a precursor solution containing aluminum hydroxide flocculent precipitate, and the concentration of the aluminum hydroxide solution is 0.3-1.0 mol / L; the mass concentration of the sodium carbonate solution is 25-35%; the concentration of the aluminum nitrate solution is 0.6-1.5 mol / L.
[0056] It can be understood that in the present invention, the precursor solution contains aluminum hydroxide, and during the spray drying and powdering process, the aluminum hydroxide is dehydrated to become aluminum oxide, thereby obtaining aluminum oxide-coated aluminum nitride and boron nitride mechanically coated composite powder containing an aluminum oxide core.
[0057] In some embodiments of the present invention, the parameters of the spray granulation tower are set as follows: furnace temperature is 100-170°C, air outlet temperature is 180-250°C, and atomizing disk rotation speed is 20-40r / s.
[0058] In some embodiments of the present invention, the particle size of the mechanical pre-coated powder is 10-100 μm.
[0059] In some embodiments of the present invention, the coated powder material comprises, from the inside to the outside, an inner aluminum oxide layer, an aluminum nitride-boron nitride layer, and an outer aluminum oxide layer; the thickness of the outer aluminum oxide layer is 2-12 μm.
[0060] In some embodiments of the present invention, the particle size of the coated powder material is 10-100 μm, preferably 15-100 μm.
[0061] The present invention forms a primary powder with fine particles of aluminum nitride and boron nitride tightly surrounding the core skeleton aluminum oxide particles by mechanical coating, and then forms an aluminum oxide layer on the surface by chemical coating to form a sandwich structure of aluminum oxide, aluminum nitride and titanium nitride, and ensures the minimum thickness of the chemically coated aluminum oxide layer, prevents the loose structure of incomplete coating of the powder particles, and improves the consistency of the powder with the original powder composition during the process of spraying to form a coating.
[0062] A second aspect of the present invention provides a method for preparing the above-mentioned coating, comprising the following steps:
[0063] S1: Substrate pretreatment: clean and dry the substrate, and then perform roughening and activation treatment on the cleaned substrate.
[0064] S2: preparing a coated powder material, spraying the coated powder material on the surface of the substrate treated in step S1 to obtain an insulating coating;
[0065] In some embodiments of the present invention, in step S1, the cleaning is performed by solvent cleaning, the solvent includes alcohol and acetone, and the drying temperature is 60-100° C. It is understandable that the cleaning can also be performed by manual wiping or ultrasonic cleaning.
[0066] In some embodiments of the present invention, in step S1, the roughening and activation treatment is: roughening and activating the surface by sandblasting. The pressure of the sandblasting is 0.1-0.6 MPa, the distance of the sandblasting is 30-140 mm, and the sand material includes white corundum with a particle size of 60 mesh.
[0067] In some embodiments of the present invention, the spraying is performed using a controlled atmosphere plasma device.
[0068] It is understandable that the usual plasma spraying process is to transport the spray powder to the center of the plasma flame through a carrier gas, and then use the high temperature and high thermal enthalpy of the flame to melt the material. At the same time, the fluid viscosity of the plasma beam is used. The high-speed plasma flame also gives the powder kinetic energy to fly, impact and deposit, and then cool and solidify on the surface of the workpiece to form a coating. The plasma beam flame of conventional atmospheric plasma spraying is directly exposed to the atmospheric environment. During the spraying process, the flying powder particles in the high-temperature molten state will come into contact with oxygen, and the boron nitride and aluminum nitride therein will be easily oxidized and decomposed, which ultimately makes the components in the coating very different from those in the original powder, and the required coating structure and coating performance cannot be achieved. The plasma of the present application uses a controlled atmosphere plasma spraying insulating coating. The atmosphere includes argon and hydrogen; wherein argon is the main gas and the protective gas acting as a controlled atmosphere, and hydrogen is the auxiliary gas.
[0069] It can be understood that the present invention adopts controlled atmosphere plasma to utilize annular argon gas flow to protect the plasma flame flow as a protective gas or to place the spraying flame flow in a container filled with argon environment to isolate it from the surrounding atmosphere, thereby directly avoiding the influence of oxidative decomposition of the powder during the spraying process, and being able to obtain a coating structure closest to the original powder composition to meet the required performance.
[0070] In some embodiments of the present invention, the process parameters of the plasma spraying are as follows: current 300-650A, voltage 50-80V, auxiliary gas flow rate 1-15L / min, scanning speed 150m / min, the energy of the plasma flame flow is adjusted by adjusting the current and auxiliary gas, powder feeding amount 20-150g / min, powder feeding carrier gas flow rate 2.0-12.0L / min, main gas flow rate 25-75L / min, main gas pressure 0.3-0.8MPa, auxiliary gas pressure 0.5-0.8MPa, spraying distance 100-250mm, spraying angle 70-90°, spraying chamber pressure (5-8)*10 -1Mpa is slightly lower than atmospheric pressure. A vacuum pump is used to extract the gas in the spraying room to take away the heat for cooling. During the entire spraying process, the surface temperature of the substrate is controlled to be ≤150℃, and the vacuum pump exhaust rate is 100-1000L / min.
[0071] S4: Sealing treatment of coating: Apply the prepared sealer evenly on the entire coating surface until it dries.
[0072] In some embodiments of the present invention, the sealing process comprises the following steps:
[0073] S4-1: The insulating coating and the workpiece on the surface prepared by the above process are cleaned with acetone, and then placed in an oven at a temperature of 100° C. (heating rate of 5-8° C. / min) for 1-3 hours;
[0074] S4-2: Then put the dried workpiece into a sealed container, inject 80℃ epoxy resin sealant into the container, and ensure that the workpiece is completely immersed in the sealant. Then evacuate the container to an absolute vacuum degree of 50-200pa, and then maintain this vacuum state for 50-100 minutes; then introduce argon or nitrogen into the sealed container to raise the pressure in the container to relative atmospheric pressure + 0.2mpa, and maintain the pressure for 60 minutes;
[0075] S4-3: Then release the pressure, take out the workpiece, remove the excess sealing agent on the surface of the workpiece, place it in an oven and heat it to 120℃ at a rate of 5-12℃ / min for 4-6h, then take it out after the oven cools down to room temperature.
[0076] The third aspect of the present invention provides a plasma spraying method for preparing an insulating coating with high thermal conductivity and self-lubricating properties using the above-mentioned coated powder, wherein the coating structure composition and uniformity are controllable.
[0077] In some embodiments of the present invention, the insulating coating prepared by plasma spraying and the transition layer on the surface of the substrate are formed by a mechanical bonding method of interactive biting of a serrated interface. There is a certain porosity of 1%-15% in the coating, the micro-Vickers hardness value of the coating is 500-1000HV, and the coating can be prepared with a thickness of 0.10-1.2mm.
[0078] The present invention will be further described below by way of examples and the like.
[0079] Example 1
[0080] A high thermal conductivity, self-lubricating insulating coating, the preparation method of which comprises the following steps:
[0081] S1: After cleaning the substrate with alcohol and drying it at 80°C, sandblasting is used to roughen and activate the surface; the sandblasting pressure is 0.4MPa and the sandblasting distance is 100mm;
[0082] S2: Prepare powder material, use controlled atmosphere plasma spraying, spray the powder material on the surface of the substrate treated in step S1 to obtain an insulating layer; wherein argon is the main gas and protective gas, and hydrogen is the auxiliary gas. The current of controlled atmosphere plasma spraying is 400A, the voltage is 50V, the auxiliary gas flow rate is 6.5L / min, the scanning speed is 150m / min, the powder feeding amount is 45g / min, the powder feeding carrier gas flow rate is 2.0L / min, the powder feeding carrier gas pressure is 0.85MPa, the main gas flow rate is 50L / min, the main gas pressure is 0.8MPa, the auxiliary gas pressure is 0.8MPa, the spraying distance is 200mm, the spraying angle is 85°, the pressure in the spraying chamber is 0.7Mpa, and the exhaust speed is 150L / min. During the spraying process, the temperature of the substrate surface is 140℃.
[0083] The preparation method of powder material is:
[0084] S2-1: By mass percentage, 25% aluminum nitride, 15% boron nitride, and 60% alumina are mixed and ball-milled for 15 hours to obtain a premixed powder; the particle size of the alumina is 3-8μm, the particle size of the boron nitride is 0.5μm, the particle size of the aluminum nitride is 0.5μm, the grinding medium is alumina balls, and the material-ball ratio is 4:10.
[0085] S2-2: According to mass percentage, 15% polyvinyl pyrrolidone, 40% polyvinyl alcohol, 10% gum arabic, 5% cyclodextrin, 25% epoxy resin and 5% carboxymethyl cellulose are mixed to obtain a binder, and the binder accounts for 6% of the total mass of the premixed powder and the binder. The premixed powder and the binder are subjected to three-stage high-speed mechanical coating and powder making in an extrusion reactor, and the powder is dried at 120°C for 3 hours and sieved to obtain a mechanical pre-coated powder with a particle size distribution of 10-25μm.
[0086] Among them, the three-stage high-speed mechanical coating includes: the first stage mechanical coating, the second stage mechanical coating and the third stage mechanical coating; the mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v1 is 500r / min, and the coating time t1 is 30min; the mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v2 is 2000r / min, and the coating time t2 is 5min; the mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v3 is 1500r / min, and the coating time t3 is 8min.
[0087] S2-3: 1000mL of a sodium carbonate solution with a mass concentration of 30% and 200mL of a 1.0mol / L aluminum nitrate solution are mixed and reacted to obtain a precursor solution, wherein the concentration of aluminum hydroxide in the precursor solution is 0.9mol / L, and the mass ratio of the mechanical pre-coated powder to the precursor solution is 1:4. After the mechanical pre-coated powder of step S2-2 is mixed with the precursor solution, the parameters of the spray granulation tower are set as follows: the furnace temperature is 120°C, the air outlet temperature is 180°C, and the atomizing disk speed is 40r / s, and spray granulation is performed to obtain a coated powder material. The particle size of the coated powder material is 10-35μm, wherein the thickness of the outer layer of aluminum oxide is 2-5μm.
[0088] S3: Sealing treatment to obtain a high thermal conductivity, self-lubricating insulating coating. The specific method of sealing treatment is: clean the insulating coating and workpiece prepared by the above process with acetone, then place it in an oven, heat it to 100℃ at 5℃ / min and bake it for 1h; then put the dried workpiece into a closed container, inject 80℃ epoxy resin sealer into the container, and ensure that the workpiece is completely immersed in the sealer. Then evacuate the container to an absolute vacuum degree of 100pa, and then maintain this vacuum state for 50min; then introduce nitrogen into the closed container to raise the pressure in the container to relative atmospheric pressure + 0.2mpa, and maintain the pressure for 60min; then release the pressure, take out the workpiece, remove the excess sealer on the surface of the workpiece, place it in an oven, heat it to 120℃ at a rate of 5℃ / min and keep it for 4h, then take it out after the oven cools down to room temperature.
[0089] Example 2
[0090] A high thermal conductivity, self-lubricating insulating coating, the preparation method of which comprises the following steps:
[0091] S1: After cleaning the substrate with alcohol and drying it at 80°C, sandblasting is used to roughen and activate the surface; the sandblasting pressure is 0.4MPa and the sandblasting distance is 100mm;
[0092] S2: Prepare powder material, use controlled atmosphere plasma spraying, spray the powder material on the surface of the substrate treated in step S1 to obtain an insulating layer; wherein argon is the main gas and protective gas, and hydrogen is the auxiliary gas. The current of controlled atmosphere plasma spraying is 500A, the voltage is 60V, the auxiliary gas flow rate is 6.5L / min, the scanning speed is 150m / min, the powder feeding amount is 45g / min, the powder feeding carrier gas flow rate is 2.0L / min, the powder feeding carrier gas pressure is 0.85MPa, the main gas flow rate is 50L / min, the main gas pressure is 0.8MPa, the auxiliary gas pressure is 0.8MPa, the spraying distance is 220mm, the spraying angle is 85°, the pressure in the spraying chamber is 0.65Mpa, and the exhaust speed is 150L / min. During the spraying process, the temperature of the substrate surface is 143°C.
[0093] The preparation method of powder material is:
[0094] S2-1: By mass percentage, 20% aluminum nitride, 15% boron nitride, and 65% alumina are mixed and ball-milled for 12 hours to obtain a premixed powder; the particle size of the alumina is 10-15μm, the particle size of the boron nitride is 0.5μm, the particle size of the aluminum nitride is 0.5μm, the grinding medium is alumina balls, and the material-ball ratio is 4:10.
[0095] S2-2: According to mass percentage, 15% polyvinyl pyrrolidone, 40% polyvinyl alcohol, 10% gum arabic, 5% cyclodextrin, 25% epoxy resin and 5% carboxymethyl cellulose are mixed to obtain a binder, and the premixed powder and the binder are subjected to three-stage high-speed mechanical coating and powder making in an extrusion reactor, so that the binder accounts for 5% of the total mass of the premixed powder and the binder. The powder is dried at 120°C for 3 hours and sieved to obtain a mechanical pre-coated powder with a particle size distribution of 20-40μm.
[0096] Among them, the three-stage high-speed mechanical coating includes: the first stage mechanical coating, the second stage mechanical coating and the third stage mechanical coating; the mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v1 is 800r / min, and the coating time t1 is 25min; the mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v2 is 2000r / min, and the coating time t2 is 5min; the mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 0.5-1cm, the rotor speed v3 is 1350r / min, and the coating time t3 is 8min.
[0097] S2-3: 1000mL of a sodium carbonate solution with a mass concentration of 30% and 200mL of a 1.0mol / L aluminum nitrate solution are mixed and reacted to obtain a precursor solution, wherein the concentration of aluminum hydroxide in the precursor solution is 0.95mol / L, and the mass ratio of the mechanical pre-coated powder to the precursor solution is 1:3.5. After the mechanical pre-coated powder of step S2-2 is mixed with the precursor solution, the parameters of the spray granulation tower are set to: the furnace temperature is 160°C, the air outlet temperature is 200°C, and the atomizing disk speed is 30r / s, and spray granulation is performed to obtain a coated powder material. The particle size of the coated powder material is 25-55μm, wherein the thickness of the outer layer of aluminum oxide is 3-8μm.
[0098] S3: Sealing treatment to obtain a high thermal conductivity, self-lubricating insulating coating. The specific method of sealing treatment is: clean the insulating coating and workpiece prepared by the above process with acetone, then place it in an oven, heat it to 100℃ at 5℃ / min and bake it for 1h; then put the dried workpiece into a closed container, inject 80℃ epoxy resin sealer into the container, and ensure that the workpiece is completely immersed in the sealer. Then evacuate the container to an absolute vacuum degree of 100pa, and then maintain this vacuum state for 50min; then introduce nitrogen into the closed container to raise the pressure in the container to relative atmospheric pressure + 0.2mpa, and maintain the pressure for 60min; then release the pressure, take out the workpiece, remove the excess sealer on the surface of the workpiece, place it in an oven, heat it to 120℃ at a rate of 5℃ / min and keep it for 4h, then take it out after the oven cools down to room temperature.
[0099] Example 3
[0100] A high thermal conductivity, self-lubricating insulating coating, the preparation method of which comprises the following steps:
[0101] S1: After cleaning the substrate with alcohol and drying it at 80°C, sandblasting is used to roughen and activate the surface; the sandblasting pressure is 0.4MPa and the sandblasting distance is 100mm;
[0102] S2: Prepare powder material, use controlled atmosphere plasma spraying, spray the powder material on the surface of the substrate treated in step S1 to obtain an insulating layer; wherein argon is the main gas and protective gas, and hydrogen is the auxiliary gas. The current of controlled atmosphere plasma spraying is 600A, the voltage is 70V, the auxiliary gas flow rate is 10.5L / min, the scanning speed is 150m / min, the powder feeding amount is 45g / min, the powder feeding carrier gas flow rate is 3.0L / min, the powder feeding gas pressure is 0.85MPa, the main gas flow rate is 75L / min, the main gas pressure is 0.8MPa, the auxiliary gas pressure is 0.8MPa, the spraying distance is 250mm, the spraying angle is 85°, the pressure in the spraying chamber is 0.55Mpa, and the exhaust speed is 300L / min. During the spraying process, the temperature of the substrate surface is 148°C.
[0103] The preparation method of powder material is:
[0104] S2-1: By mass percentage, 18% aluminum nitride, 12% boron nitride, and 70% alumina are mixed and ball-milled for 10 hours to obtain a premixed powder; the particle size of the alumina is 15-25μm, the particle size of the boron nitride is 1μm, the particle size of the aluminum nitride is 1μm, the grinding medium is alumina balls, and the material-ball ratio is 3:10.
[0105] S2-2: According to mass percentage, 15% polyvinyl pyrrolidone, 40% polyvinyl alcohol, 10% gum arabic, 5% cyclodextrin, 25% epoxy resin and 5% carboxymethyl cellulose are mixed to obtain a binder, and the binder accounts for 4.5% of the total mass of the premixed powder and the binder. The premixed powder and the binder are subjected to three-stage high-speed mechanical coating and powder making in an extrusion reactor, and the powder is dried at 120°C for 3 hours and sieved to obtain a mechanical pre-coated powder with a particle size distribution of 30-50μm.
[0106] Among them, the three-stage high-speed mechanical coating includes: the first stage mechanical coating, the second stage mechanical coating and the third stage mechanical coating; the mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 1-2cm, the rotor speed v1 is 1000r / min, and the coating time t1 is 25min; the mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 1-2cm, the rotor speed v2 is 2000r / min, and the coating time t2 is 5min; the mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 1-2cm, the rotor speed v3 is 1200r / min, and the coating time t3 is 8min.
[0107] S2-3: 850 mL of a sodium carbonate solution with a mass concentration of 35% and 200 mL of a 1.0 mol / L aluminum nitrate solution are mixed and reacted to obtain a precursor solution, wherein the concentration of aluminum hydroxide in the precursor solution is 1.0 mol / L, and the mass ratio of the mechanical pre-coated powder to the precursor solution is 1:3. After the mechanical pre-coated powder of step S2-2 is mixed with the precursor solution, the parameters of the spray granulation tower are set as follows: the furnace temperature is 170°C, the air outlet temperature is 240°C, and the atomizing disk speed is 25 r / s, and spray granulation is performed to obtain a coated powder material. The particle size of the coated powder material is 35-60 μm, wherein the thickness of the outer layer of aluminum oxide is 1-3 μm.
[0108] S3: Sealing treatment to obtain a high thermal conductivity, self-lubricating insulating coating. The specific method of sealing treatment is: clean the insulating coating and workpiece prepared by the above process with acetone, then place it in an oven, heat it to 100℃ at 5℃ / min and bake it for 1h; then put the dried workpiece into a closed container, inject 80℃ epoxy resin sealer into the container, and ensure that the workpiece is completely immersed in the sealer. Then evacuate the container to an absolute vacuum degree of 100pa, and then maintain this vacuum state for 50min; then introduce argon or nitrogen into the closed container to raise the pressure in the container to relative atmospheric pressure + 0.2mpa, and maintain the pressure for 60min; then release the pressure, take out the workpiece, remove the excess sealer on the surface of the workpiece, place it in an oven, heat it to 120℃ at a rate of 5℃ / min and keep it for 4h, then take it out after the oven cools down to room temperature.
[0109] Comparative Example 1
[0110] A homogeneous aluminum oxide coating, the preparation method of which comprises the following steps:
[0111] S1: After cleaning the substrate with alcohol and drying it at 80°C, sandblasting is used to roughen and activate the surface; the sandblasting pressure is 0.4MPa and the sandblasting distance is 100mm;
[0112] S2: Take aluminum oxide powder with a purity of 99.5% and a powder particle size of 15-54μm, and use atmospheric plasma spraying to spray the powder material on the surface of the substrate treated in step S1 to obtain an insulating layer; wherein the parameters of atmospheric plasma spraying are: current of 400A, voltage of 50V, auxiliary gas flow rate of 5L / min, scanning speed of 150m / min, powder feeding amount of 50g / min, powder feeding carrier gas flow rate of 2.0L / min, main gas flow rate of 50L / min, main gas pressure of 0.8MPa, auxiliary gas pressure of 0.8MPa, spraying distance of 200mm, spraying angle of 85°, and cooling pressure of 0.4Mpa. During the spraying process, the temperature of the substrate surface is 128℃.
[0113] S3: Sealing treatment to obtain a high thermal conductivity, self-lubricating insulating coating. The specific method of sealing treatment is: clean the insulating coating and workpiece prepared by the above process with acetone, then place it in an oven, heat it to 100℃ at 5℃ / min and bake it for 1h; then put the dried workpiece into a closed container, inject 80℃ epoxy resin sealer into the container, and ensure that the workpiece is completely immersed in the sealer. Then evacuate the container to an absolute vacuum degree of 100Pa, and then maintain this vacuum state for 50min; then introduce argon or nitrogen into the closed container to raise the pressure in the container to relative atmospheric pressure + 0.2Mpa, and maintain the pressure for 60min; then release the pressure, take out the workpiece, remove the excess sealer on the surface of the workpiece, place it in an oven, heat it to 120℃ at a rate of 5℃ / min and keep it for 4h, then take it out after the oven cools down to room temperature.
[0114] Comparative Example 2
[0115] Comparative Example 2 is the same as Example 1, except that it does not contain chemical coating, that is, it does not contain step S2-3, and the other conditions are the same as Example 1.
[0116] Comparative Example 3
[0117] Comparative Example 3 is the same as Example 1, except that in the mechanical coating, the speeds and times of the three stages are different.
[0118] In Comparative Example 3, the premixed powder was mixed with a binder and then subjected to three-stage high-speed mechanical coating and powder making in an extrusion reactor, dried at 120° C. for 3 hours, and sieved to obtain a mechanical pre-coated powder with a particle size distribution of 25-55 μm.
[0119] Among them, the three-stage high-speed mechanical coating includes: the first stage mechanical coating, the second stage mechanical coating and the third stage mechanical coating; the mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v1 is 500r / min, and the coating time t1 is 30min; the mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v2 is 1500r / min, and the coating time t2 is 8min; the mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 0.5-1.5cm, the rotor speed v3 is 2000r / min, and the coating time t3 is 5min.
[0120] Comparative Example 4
[0121] Comparative Example 4 is the same as Example 1, except that the premixing process of step S2-1 is not included, and the boron nitride, aluminum nitride, aluminum oxide and the binder are directly mixed. The rest is the same as Example 1.
[0122] Test example:
[0123] The coatings prepared in the embodiments of the present invention and the comparative examples were tested, as shown in Table 1. The thermal conductivity was measured by using a laser thermal conductivity meter at 25°C and 3 flash points, and the insulation performance was measured by using a 3000V / AC AC tester at an air humidity of 10-40% after sealing. The bonding strength was tested by using a universal tensile machine to obtain the results. The sliding friction coefficient was obtained by using a friction coefficient meter to test the coating friction coefficient.
[0124] Table 1 Test results of embodiments and comparative examples
[0125]
[0126]
[0127] It can be seen from Table 1 that although the aluminum nitride and boron nitride in the insulating material of the present invention slightly sacrifice the electrical insulation performance of the coating to a certain extent, they significantly improve the thermal conductivity of the alumina ceramic coating, increase the self-lubricating function of the coating, and reduce the friction coefficient of the coating.
[0128] By testing the electrical insulation properties of the coating prepared in the embodiment of the present invention under different air humidity, it can be known that the electrical insulation properties of the self-lubricating high thermal conductive insulating coating in the present invention at 3000V under air humidity of 10-40%, 40-70%, and 70-95% are 15-70GΩ, 10-55GΩ, and 8-35G, respectively.
[0129] Under an AC voltage of 3000V, the power frequency voltage characteristic detection current value is less than 20mA. The breakdown voltage of the insulating coating of the present invention is tested using an AC breakdown tester, and the breakdown voltage is greater than 5000V.
[0130] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity, self-lubricating insulating coating, characterized in that: The preparation method comprises the following steps: S1: After cleaning and drying the substrate, the substrate is subjected to surface treatment and then used for standby; S2: spraying the powder material on the surface of the substrate treated in step S1 to obtain an insulating layer; S3: Sealing treatment to obtain a high thermal conductivity, self-lubricating insulating coating; In step S2, the powder material is prepared by: S2-1: premixing aluminum oxide powder, aluminum nitride powder, and boron nitride powder to obtain a premixed powder; S2-2: subjecting the premixed powder and the additive to three-stage high-speed mechanical coating and powdering in an extrusion reactor to obtain mechanical pre-coated powder; S2-3: mixing the mechanical pre-coated powder of step S2-2 with the precursor solution, and spray drying in a spray granulation tower to obtain a coated powder material; The premixed powder comprises the following components by mass percentage: 15%-25% aluminum nitride, 10%-25% boron nitride, and 50%-75% aluminum oxide; wherein the particle size of the aluminum oxide is 1-50 μm, the particle size of the boron nitride is 0.1-5 μm, and the particle size of the aluminum nitride is 0.1-5 μm; The mass ratio of the mechanical pre-coated powder to the precursor solution is 1: (1-9); the precursor solution is a precursor solution containing aluminum hydroxide flocculent precipitate obtained by mixing and reacting a sodium carbonate solution and an aluminum nitrate solution; the mass concentration of the sodium carbonate solution is 25-35%; the concentration of the aluminum nitrate solution is 0.6-1.5 mol / L; The coated powder material comprises, from the inside to the outside, an inner layer of aluminum oxide, an aluminum nitride-boron nitride layer, and an outer layer of aluminum oxide; In step S2-1, the premixing is ball milling; the ball milling time is 8-15 hours, and the ball milling medium is alumina balls; In step S2-2, the selected auxiliary agent is a binder; the binder accounts for 1%-10% of the total mass of the premixed powder and the binder; The three-stage high-speed mechanical coating includes: a first stage mechanical coating, a second stage mechanical coating and a third stage mechanical coating; in, The mechanical coating conditions of the first stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v1 is 500-1600 r / min, and the coating time t1 is 10-30 min; The mechanical coating conditions of the second stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v2 is 1500-2500 r / min, and the coating time t2 is 5-10 min; The mechanical coating conditions of the third stage include: the distance between the extrusion head and the kettle wall is 0.5-4 cm, the rotor speed v3 is 800-1500 r / min, and the coating time t3 is 6-15 min; In the three-stage highly mechanical coating powder making, the rotor speed and coating time satisfy the following relationship: v1<v3<v2, and t1>t3>t2.
2. The preparation method according to claim 1, characterized in that: In step S1, the surface treatment is to roughen and activate the surface by sandblasting; the pressure of the sandblasting is 0.1-0.6 MPa, and the distance of the sandblasting is 30-140 mm.
3. The preparation method according to claim 1, characterized in that: In step S2, the spraying is carried out by controlled atmosphere plasma spraying, wherein argon is used as the main gas and the protective gas, and hydrogen is used as the auxiliary gas.
4. The preparation method according to claim 3, characterized in that: The parameters of the controlled atmosphere plasma spraying are: current 300-650A, voltage 50-80V, auxiliary gas flow rate 1-15L / min, scanning speed 150m / min, powder feeding amount 20-150g / min, powder feeding carrier gas flow rate 2.0-12.0L / min, main gas flow rate 25-75L / min, main gas pressure 0.3-0.8MPa, auxiliary gas pressure 0.5-0.8MPa, spraying distance 100-250mm, spraying angle 70-90°, and pressure in the spraying chamber 0.5-1.0Mpa.
5. The preparation method according to claim 1, characterized in that: In step S2, during the spraying process, the temperature of the substrate surface is ≤150°C.
6. The preparation method according to claim 1, characterized in that: In step S2-3, The parameters of the spray granulation tower are set as follows: furnace temperature is 100-170°C, air outlet temperature is 180-250°C, and atomizing disk speed is 20-40r / s; The thickness of the outer layer of aluminum oxide is 2-12 μm; The particle size of the coated powder material is 10-100 μm.
7. The preparation method according to claim 1, characterized in that: In step S2-3, the particle size of the coated powder material is 15-100 μm.
8. A high thermal conductivity, self-lubricating insulating coating prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The thickness of the coating is 0.10-1.2 mm.
Citation Information
Patent Citations
Boron nitride film preparation method and boron nitride film
CN115820009A
Preparation method and application of aluminum oxide coated hexagonal boron nitride composite powder
CN116376321A
Insulating thermal conductive composite ceramic powder, preparation method and application thereof and insulating thermal conductive coating
CN109369158A
Preparation method of insulating coating for bearing
CN112410718A
Preparation method of mechanically mixed coated powder and coated powder
CN115608984A
